Molecular Characterization of the Porcine Group A Rotavirus NSP2 and NSP5/6 Genes from São Paulo State, Brazil, in 2011/12. (15th July 2013) - Barbosa, Bruna Rocha Passos; Bernardes, Nara Thiers Cacciatori Galleti; Beserra, Laila Andreia Rodrigues; Gregori, Fábio
Abstract : Rotaviruses are responsible for the acute diarrhea in various mammalian and avian species. The nonstructural proteins NSP2 and NSP5 are involved in the rotavirus replication and the formation of viroplasm, cytoplasmic inclusion bodies within which new viral particles morphogenesis and viral RNA replication occur. There are few studies on the genetic diversity of those proteins; thus this study aims at characterizing the diversity of rotavirus based on NSP2 and NSP5 genes in rotaviruses circulating in Brazilian pig farms. For this purpose, 63 fecal samples from pig farms located in six different cities in the São Paulo State, Brazil, were screened by nested RT-PCR. Seven strains had the partial nucleotide sequencing for NSP2, whereas in six, the total sequencing for NSP5. All were characterized as genotype H1 and N1. The nucleotide identity of NSP2 genes ranged from 100% to 86.4% and the amino acid identity from 100% to 91.5%. For NSP5, the nucleotide identity was from 100% to 95.1% and the amino acid identity from 100% to 97.4%. It is concluded that the genotypes of the strains circulating in the region of study are in agreement with those reported in the literature for swine and that there is the possibility of interaction between human and animal rotaviruses.